The effect of macromolecular crowding on mobility of biomolecules, association kinetics, and gene expression in living cells - Tabaka, Marcin; Kalwarczyk, Tomasz; Szymanski, Jedrzej; Hou, Sen; Holyst, Robert (Frontiers in Physics, 2014)
We discuss a quantitative influence of macromolecular crowding on biological processes: motion, bimolecular reactions, and gene expression in prokaryotic and eukaryotic cells. We present scaling laws relating diffusion coefficient of an object moving in a cytoplasm of cells to a size of this object and degree of crowding. Such description leads to the notion of the length scale dependent viscosity characteristic for all living cells. We present an application of the length-scale dependent viscosity model to the description of motion in the cytoplasm of both eukaryotic and prokaryotic living cells. We compare the model with all recent data on diffusion of nanoscopic objects in HeLa, and E. coli cells. Additionally a description of the mobility of molecules in cell nucleus is presented. Finally we discuss the influence of crowding on the bimolecular association rates and gene expression in living cells.